Optimalisasi Infrastruktur Jaringan Menggunakan Link Aggregation Control Protocol Dengan Device Cloud Router Switch - Subandri Subandri; Zaenal Mutaqin Subekti (Jurnal Informatika: Jurnal Pengembangan IT, 2019)
The development of data in a company is getting bigger and requires fast access time. the existence of a system that uses computer networks and internet access to support the activities of the company becomes an important part in the use of infrastructure in the company. Computer networks are accessed by all staff and employees in the building and there are servers and databases that are accessed all the time. In the building part consists of several work processes that simultaneously access to the same network and server. Then each staff and employee will access the same network infrastructure, where the data transfer burden is delegated to only one (1) switch port to connect. This can result in a large burden and network access can be slowed. By providing a configuration to optimize the switch network that adopts the link agro-protocol protocol (LACP) method on the use of network infrastructure so that it can be a solution for overcoming large network loads and slow access. By applying PPDIOO to the infrastructure development method so that the expectations can be achieved in accordance with the desired results